Slow 0.9% NaCl Bolus Administration Reduces ANP, MMP-2, and Syndecan-1 Shedding in Septic Shock Rabbit Models - Hartawan, I Nyoman Budi; Wiryana, Made; Jawi, I Made; Astawa, I Nyoman Mantik; Bakta, I Made; Subanada, Ida Bagus; Suparyatha, Ida Bagus; Wati, Dyah Kanya (Cell and BioPharmaceutical Institute, 2025)
Background: The optimal rate for fluid bolus administration in septic shock remains a critical and unresolved question. Rapid bolus administration is commonly practiced but has been linked to elevated levels of atrial natriuretic peptide (ANP), matrix metalloproteinase-2 (MMP-2), and syndecan-1 shedding, potentially exacerbating endothelial glycocalyx damage and increasing vascular permeability. However, the physiological and clinical implications of slower bolus rates have not been thoroughly investigated. This study was conducted to identify safer fluid management practices and improve patient outcomes in septic shock.Materials and methods: A randomized post-test-only control group design was employed, involving 36 male New Zealand rabbits with lipopolysaccharide-induced septic shock. The treatment group received 0.9% NaCl boluses (20 mL/kg body weight) over 20 minutes per bolus (slow bolus), while the control group received the same volume over 5 minutes per bolus (rapid bolus). ANP, MMP-2, and syndecan-1 levels were measured using ELISA 10-15 minutes post-intervention.Results: The median ANP levels in the treatment group (92.86 ng/mL) were significantly lower (p<0.05) than those in the control group (367.32 ng/mL). The mean MMP-2 levels in the treatment group (10.26 ng/dL) were lower than those in the control group (11.43 ng/dL). The median levels of syndecan-1 were also lower in the treatment group (4.31 ng/mL) compared to the control group (5.94 ng/mL).Conclusion: Slow fluid boluses appear to mitigate endothelial damage by reducing ANP, MMP-2, and syndecan-1 shedding. These findings suggest that slower infusion rates may offer a protective advantage in fluid resuscitation, paving the way for updated clinical guidelines.Keywords: fluid bolus, ANP, MMP-2, syndecan-1